Internet Addiction Among Collegiates and Its Impact on Sleep Quality, Stress and Physical Activity: A Cross-Sectional Study - Siwach, Vinika; Bhati, Pooja; Hussain, M. Ejaz (Journal of Neonatal Surgery, 2025)
Background: Internet usage has been rapidly increasing among the collegiate population and its prevalence rate is around 37% among Indian collegiate students. Its negative impacts are evident in university students' numerous health-related areas. Thus, the purpose of this study is to determine how internet addiction affects sleep, stress levels, and physical activity levels in collegiates. Method: A total of 118 students, both male and female, between the ages of 18 and 26, participated in this cross-sectional study. They were divided into three groups according to their scores on the Young's Internet Addiction Test (YIAT): Group A- no internet addiction, Group B- mild internet addiction, Group C- moderate to severe internet addiction. The Pittsburgh Sleep Quality Index (PSQI), the Perceived Stress Scale (PSS), and the International Physical Activity Questionnaire (IPAQ-SV) were used to measure the participants' sleep quality and levels of stress and physical activity. Result: The findings showed that, of the 118 participants, 33.89% (40) had moderate to severe online addiction, whereas 27.96% (33) had mild internet addiction. When comparing moderate to severe internet users to those without internet addiction, significant differences were found in their levels of stress, physical activity, and sleep quality. Furthermore, a significant positive correlation was found between PSQI and PSS score whereas negative correlation between IPAQ with internet addiction score. Conclusion: Internet addiction is associated with poor sleep quality, increased stress level as well as reduces physical activity among the collegiates.